1997
DOI: 10.1055/s-0038-1657677
|View full text |Cite
|
Sign up to set email alerts
|

Variable Platelet Response to Low-dose ASA and the Risk of Limb Deterioration in Patients Submitted to Peripheral Arterial Angioplasty

Abstract: SummaryA group of 100 patients with intermittent claudication (70 male, 30 female), treated with 100 mg ASA per day, were followed over 18 months after elective percutaneous balloon angioplasty. Platelet function was monitored over a period of 12 months by corrected whole blood aggregometry (CWBA). Upon stimulation by arachidonic acid (AA), adenosine diphosphate (ADP) and collagen, CWBA-results were obtained by an electronic acquisition and evaluation system correcting for hematocrit and platelet count of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
175
0
10

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(193 citation statements)
references
References 28 publications
8
175
0
10
Order By: Relevance
“…43,58,64,82,83 These interesting findings, if confirmed in larger studies, could bear important clinical implications, because they suggest that monitoring platelet function during antiplatelet therapy can be useful to predict the risk of treatment failures. However, the phenomenon that they describe should not be termed "aspirin resistance," because it is determined to a large extent by variables that cannot be inhibited by aspirin.…”
Section: Unproven Aspirin Resistancementioning
confidence: 85%
“…43,58,64,82,83 These interesting findings, if confirmed in larger studies, could bear important clinical implications, because they suggest that monitoring platelet function during antiplatelet therapy can be useful to predict the risk of treatment failures. However, the phenomenon that they describe should not be termed "aspirin resistance," because it is determined to a large extent by variables that cannot be inhibited by aspirin.…”
Section: Unproven Aspirin Resistancementioning
confidence: 85%
“…Nevertheless, the phenomenon appears real, however defined, and 4 reports suggest that patients with aspirin resistance are at increased risk for thrombotic complications. 20,21,32,33 Additionally, the concomitant administration of ibuprofen seems to antagonize the irreversible platelet inhibition induced by aspirin 34 and may also be associated with increased thrombotic complications. 35,36 Clopidogrel offers added antiplatelet efficacy to aspirin in patients with acute coronary syndromes 3 or after stent implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Some study the prevalence of aspirin resistance and how to achieve defining its presence, [6][7][8] some study the mechanisms for aspirin resistance, [9][10][11][12] and yet others examine the impact or clin-ical significance of aspirin resistance on the presence or development of cardiovascular disease [13][14][15][16][17][18][19][20][21] (Table I). There is no consensus on the ideal technique for the assessment of the presence of aspirin resistance and therefore no agreement about a standardized definition.…”
Section: Discussionmentioning
confidence: 99%
“…These prostaglandins may promote aspirin resistance through platelet aggregation and vasoconstriction. 24,28 Clinical Implications of Aspirin Resistance Few long-term clinical studies have examined the clinical significance of aspirin resistance (Table I) 13,[15][16][17][19][20][21] Mueller et al 13 studied 100 patients undergoing peripheral balloon angioplasty and found that aspirin-resistant patients had an 87% higher risk of vascular reocclusion after 18 months. Sane et al 16 found an increased prevalence of aspirin resistance in patients post coronary artery bypass during their most vulnerable period, which was the first 5-10 days post surgery.…”
Section: Mechanisms Of Aspirin Resistancementioning
confidence: 99%